Research based history learning model as the effort to strengthen character education and knowledge in SMAN 2 Bantul - Bayu Ananto Wibowo (Journal of Social Studies (JSS), 2018)
The purpose of research was to find out: (1) The implementation of research-based learning model in SMAN 2 Bantul as a learning innovation of Curriculum 2013, (2) The implementation of research-based learning model in History learning in SMAN 2 Bantul. This research was a qualitative descriptive research using the qualitative approach of case study in SMAN 2 Bantul. Research subjects were the principal, the curriculum coordinator, the History teachers, and the students. The data obtained in the research were in the form of direct information from the subject, the observation and facts documents in the field in accordance with the research focus. The process of testing the data validity done in this research included the triangulation and reference materials. The data analysis techniques used in this research was Miles and Huberman’s model that were data reduction, data display, and conclusion drawing / verification. The results of the study are as follows: (1) Research-based learning model can be a role model for other senior high schools that implement Curriculum 2013. In its application in the school, this learning model was being regularized extracurricular for grade X students, as the introduction to research until the real practice in the field, hoping that when they become grade XI and XII students, this research-based learning can be applicable to each subject. Besides, this learning model can strengthen the character education and also deepen the knowledge of the students. (2) In History learning, this research-based learning model can improve students' thinking ability that can be seen from their ability in discussing and expressing opinion that was much better than before. The research-based learning model applied to the History learning created a new learning model that was named the Research-Based History Learning Model.